Analysis of Cardiorespiratory Endurance Levels of High School Futsal Teams - M. Said Zainuddin; Slamet Riyadi; Ahmad Zakaria (Journal Coaching Education Sports, 2023)
This study aims to find out how good the cardiorespiratory endurance level of the SMA Negeri 22 Makassar futsal team is. This research is a quantitative descriptive research, the test technique used to collect data is the Multistage Fitness Test. The population in this study was 25 futsal team players at SMA Negeri 22 Makassar, the sample to determine the population used purposive sampling. The data analysis technique used is descriptive statistics in the form of percentages. The prevalence of "fair" (moderate) fitness levels among players under the age of 18 in the futsal team of SMA Negeri 22 Makassar indicates the need for a targeted training program to improve their cardiorespiratory endurance. With 62.5% of respondents falling into this category, this shows the potential to increase their fitness levels to achieve better performance on the field. Identifying factors contributing to lower fitness levels among the 37.5% of players categorized as “poor” (poor) may provide valuable insight for developing personalized training interventions and plans to meet their specific needs. By addressing these fitness gaps, teams can potentially improve their overall performance and competitiveness in futsal tournaments. A sufficient level of cardiorespiratory endurance is important in the sport of futsal, which involves fast movements, sudden changes in direction, and high intensity. By having a sufficient level of cardiorespiratory endurance, SMA Negeri 22 Makassar futsal players can maintain their performance during matches, reduce fatigue and minimize the risk of injury.